The Council of Castile and the witches of Biscay. An example of the Royal Council competence development in the seventeenth century - Bernal Alonso, Eva (Huarte de San Juan. Geografía e Historia, 2013)
The Council of Castile suffered one of the major reorganizations of its existence in the early seventeenth century: the creation of the Government Board. This new Board was responsible for handling all gubernatorial business from Castile and also intervened in matters which were outside its natural scope. Witchcraft was an example. Given the inactivity both of the Inquisition and the mayor, the Lordship of Biscay asked the Council of Castile to stop the many cases of witchcraft that emerge at their territory.
Keywords: Council of Castile; lordship of Biscay; inquisition; corregimientos; witches